Creating a city centre in coastal area: The case of New City Centre of Kocaeli - Yildiz, Reyhan; Şenlier, Nihâl; Uzun, Nilay Sonmez (Mediterranean Coastal Foundation, 2017)
Since the mid 1960s, coastal areas have become the common areas for the implementation of urban regeneration projects in USA, UK and many other countries. Urban development in coastal areas is seen as an important tool, especially for the solution of urban problems, attraction of global capital and inter-city competitions. Also, these areas are the identity areas supported by political and economic trends and reflecting the cosmopolitan city life. Regeneration projects shape the relationships between places, usages and the visions and offer outstanding opportunities by investigating the harbour, city functions and their economic, environmental and social aspects. Although urban waterfronts took the American cities as a model in the beginning, in time, some negative experiences in European coastal areas showed that standardized regeneration models did not bring the best local solutions and cities have started to bring their own approaches. Regeneration projects have undergone a transition from single-functioned and small-scale approaches to large-scale strategic perspectives, and integrated with medium and long-term sustainable urban renewal studies. Coastal areas and urban waterfronts have begun to be seen as an important part of the broader concept of the city and the region. This study aims to bring suggestions on the planning and design processes of waterfront regeneration projects of Turkey by examining the development process of similar projects around the world. In this respect, the recent experience on the Izmit waterfront (New City Centre of Kocaeli) regeneration process is going to be evaluated as a case study. This planning practice can be distinguished as a successful example with regard to adoption of participatory and new institutional collaborative planning approaches, understanding of contribution of consensus building in regeneration process. On the other hand, the project has received great criticism from professional associations and non-governmental organisations for not providing sufficient sensitivity to protect wetland in the region and its rant-oriented approach. © 2018 Elsevier B.V., All rights reserved.
13th International MEDCOAST Congress on Coastal and Marine Sciences, Engineering, Management and Conservation, MEDCOAST 2017 -- Mellieha; Paradise Bay Resort Hotel -- 132081
Keywords: Social aspects; Urban growth; Collaborative planning; Consensus buildings; Negative experiences; Non-governmental organisations; Professional associations; Regeneration process; Strategic perspectives; Waterfront regeneration; Coastal zones